TEC Data Forecasting Using a Novel Nonlinear Model - Jun Wang (Advances in Astronomy, 2015)
A novel nonlinear TEC forecasting model is proposed in the paper; the main produces of the model are as follows: first the EOF decomposition of TEC data is made, then the genetic algorithm is used to establish the nonlinear time field model, and finally the decomposed space field and the predicted time field are reconstructed to achieve the purpose of forecasting the TEC data. Experiments indicate that the performance of the novel forecasting model is effective and superior to the direct forecasting and linear forecasting models.